Development of a “pinhão” (brazilian pine nut) peeling machine - Nagaoka, Alberto Kazushi (2019)
The pine nut production’s chain involves stages such as harvesting, peeling, industrialization and commercialization. One of the bottlenecks pointed by producers is the lack of equipments capable of peeling the product, increasing the work capacity of the activity. The peeling of this seed is a difficult and time consuming process, requiring the use intense labor utilization. The main objective of this research is to develop a pine nut peeling’s machine. The research was based on a methodology which focuses on the industrial products’ development, composed by different stages (Project’s planning, Informational Project, Conceptual Project, Preliminar Project and detailed Project). The systematic application adopted has allowed effectiveness in the project’s development and in the prototype’s construction. The pinion peeling machine using 3cm diameter straight grooved cylinders offered better performance with handling capacity of 24.6 kg h-1 and efficiency of 61% and the best speed obtained was 0,0157 m s-1, being considered adequate to the conditions of use of the family producers of Serra Catarinense.